Pemanfaatan Pangan Unggul Daerah Dalam Pencegahan Stunting: Pembuatan Nugget Berbahan Daun Kelor dan Tempe - Rina Kudadiri; Fadli Afriandi (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2023)
The problem in the world today, especially in developing countries, is stunting or slow growth for children of the same age. Stunting is caused by multidimensional factors, such as a lack of nutritional intake, which can impact the level of intelligence, so nutritious food is needed, which can prevent stunting. Rambong Village is a village that has regional potential and is rich in Moringa plants and tempeh production. These two ingredients are full of nutritional potential; tempeh contains vegetable protein, which is very easy to access. Moringa leaves are used in malnutrition, such as improving breast milk (breast milk). This huge potential is utilized to make nugget products such as Supplementary Feeding (PMT). Nuggets are made because this food is a favorite among the people. This activity was carried out at Meunasah Baro, Rambong Village, Beuracan, Meuredu District, Pidie Jaya Regency on June 12, 2023. Thirty mothers and 15 children attended this activity. This activity was carried out by delivering material related to stunting and efforts to prevent stunting from occurring through PMT. From the service that has been carried out, community participation is obtained in utilizing local food to be processed into additional food to meet nutritional adequacy.